REFERENCE EVAPOTRANSPIRATION FOR DESIGN OF IRRIGATION SYSTEMS IN PETROLINA, BRAZIL - da Silva, A. O.; Correia, J. de S.; Bassoi, L. H.; Teixeira, A. H. de C. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Evapotranspiration is a key variable to estimate crop water requirement, to support the design of pumping systems, supply and distribution of water for irrigation. The distribution frequence of reference evapotranspiration (ETo) estimated by class A pan in Petrolina, State of Pernambuco, Brazil, was characterized based on a series of 45 years (1963 - 2010), grouped in periods of 5,10,15 and 30 days. Gamma and Normal distributions were applied to the ETo data with a probability of 95, 90, 75, 50, 25, 10 and 5%. The Normal and gamma distributions were able to represent the data of reference evapotranspiration for the cumulative periods of 10, 15 and 30 days. The ETo values ​​(11.06 and 11.07 mm day-1, normal and gamma distribution, respectively) for the month of October in the period from 15 days with 75% probability were the most suitable for the scaling of the maximum daily depth projects of irrigation systems.